Cross-lagged analysis of social support, physical activity behavior, and family relationships among university students - Zhou, Xielin; Zhang, Mu; Li, Bo; Ma, Shasha (Frontiers in Psychology, 2024)
Objective: To explore the causal relationship between social support, physical activity behavior, and family relationships among university students. Methods: Using the Social Support Rating Scale, the Physical Activity Behavior Self-Assessment Scale, and the Family Relationships Scale, a longitudinal follow-up survey was conducted on 412 college students in Sichuan Province at 2-month intervals in March 2024 (T1) and May 2024 (T2), to analyze the interaction mechanisms between college students' social support, physical activity behaviors, and family relationships through crosslagging. Results: (1) There are significant gender differences in social support, physical activity behavior, and family relationships among college students. Among the cross-lagged paths found, except for the path from T1 social support to T2 family relationships (β: 0.40 > 0.21), all other crosslagged paths are smaller for female college students compared to male college students; (2) T1 social support was able to positively predict T2 physical activity behaviors (β = 0.50, p<0.001), and T1 physical activity behavior can also positively predict T2 social support (β=0.18, p<0.01), but the path value T1 social support → T2 physical activity behavior is larger than T1 physical activity behavior → T2 social support. Therefore, social support is a causal variable for physical activity behavior; (3) T1 social support positively predicts T2 family relationships (β=0.26, p<0.001); (4) T1 family relationships positively predict T2 physical activity behavior (β=0.30, p<0.001). ( 5) Physical activity behavior is a mediating variable between family relationships and social support, with a mediating effect size of 0.054. Conclusion: there are gender differences in social support, physical activity behavior, and family relationships among college students; there is a longitudinal causal relationship between social support, physical activity behavior, and family relationships; social support is a causal variable of physical activity behavior, and social support is also a causal variable of family relationships, and family relationships are the Social support is a causal variable for physical activity behavior, social support is also a causal variable for family relations, and family relations are a causal variable for physical activity behavior, which has a partially mediating role in family relations and social support.